Waqf Blockchain in Indonesia - Lu'liyatul Mutmainah; Nurwahidin; Nurul Huda (Badan Wakaf Indonesia, 2021)
Abstract: The emergence of innovation in the world of digital finance in recent years has received attention from various parties commonly known as financial technology. This innovation is in the form of crowdfunding and blockchain platforms. These two innovations can not only be used for commercial, but also social purposes, including waqf. There is a huge potential of cash waqf in Indonesia. However, the realization is relatively still low. This study aims to analyze at a glance waqf blockchain in Indonesia that can optimize the realization of waqf development in Indonesia. Qualitative research methods is used in this paper through the study of literature. The results of the study show that Indonesia is very likely to implement waqf blockchain because the Muslim population reaching more than 80%, the flexible concept of waqf fiqh and the emergence of the halal industry. The most challenges faced are related to waqf literacy to increase public awareness. Investigating about perceived intention to use waqf blockchain through questionnaire and a deep interview with the stakeholders is important for the future research. Keywords: technology, blockchain, waqf.